African female doctoral graduates account for success in their doctoral journeys - Tsephe, Lifutso (HTS teologiese studies, 2022)
Doctoral education is regarded as a crucial engine for development by the knowledge economies, thereby making the research capacity of scholars play a critical factor towards development. Widening participation within doctoral education is seen as a way of enhancing this capacity. However, African scholars produce only 1.4% of all published research, indicating that Africa lacks research capacity. Even though both men and women contribute to the development of their continent and their countries, the number of women holding doctoral degrees on the African continent remains low across all nationalities. In high-income countries, there are 3963 PhDs per million people, whereas in some African countries (such as Tunisia, Egypt and Kenya), the number ranges from 100 to over 1500; however, in most low-income countries (such as Ethiopia, Uganda and Tanzania), the number is less than 100. Much research in doctoral education examines the reasons for low graduation rates and high attrition rates, but little research examines the contributors to the doctoral study for African women, especially in these times when doctoral education is viewed as a driver of the economy. Based on a qualitative study that interviewed 14 women from African countries, this article aimed to investigate how women account for completing doctoral studies. Data were gathered through semistructured interviews and analysed thematically using a capabilities approach as a theoretical framework. The findings suggest that institutional support, peer support and academic support played a role in their achievement.Contribution: The article contributed to doctoral education scholarship of African women and indicated that religion contributed to African women’s success in doctoral programmes, granting them strength to push until completion. This research may greatly encourage more women to enrol in doctoral programmes when reading other women’s success stories.